Environmental Conditions and Vegetation Recovery at Abandoned Drilling Mud Sumps in the Mackenzie Delta Region, Northwest Territories, Canada - Johnstone, Jill F.; Kokelj, Steven V. (ARCTIC, 2009)
Historical data from oil and gas exploration in the delta of the Mackenzie River, Northwest Territories, in the 1970s provided an opportunity to estimate decadal-scale impacts of exploratory oil and gas drilling on native plant communities in low Arctic tundra. We assessed changes in vegetation composition and associated environmental gradients across seven drilling mud sumps in the Kendall Island Bird Sanctuary, Mackenzie Delta. Three decades after disturbance, drilling sumps had developed vegetation coverage equivalent to that in undisturbed areas, although bare soil persisted in ponded areas and where a salt crust was present. Vegetation on sumps was composed of communities dominated by forbs, grasses, and tall shrubs that were distinct from adjacent, undisturbed sedge and low shrub communities. The area of altered vegetation around a sump was generally larger in upland or saline environments than in lowland areas. Pooled water observed around many sumps was likely associated with thaw subsidence that occurred following construction, which was subsequently compounded by snow drifting and increased soil temperatures along the margins of the sump mound. Changes in drainage, active-layer depth, and surface salt concentrations appear to be key environmental factors that have helped shape plant communities established on drilling sumps in the three decades after disturbance. Les données historiques relatives à l’exploration pétrolière et gazière réalisée dans le delta du fleuve Mackenzie, Territoires du Nord-Ouest, dans les années 1970 ont permis d’estimer les incidences décadaires des forages pétroliers et gaziers exploratoires sur les peuplements de végétaux régionaux de la basse toundra arctique. Nous avons évalué les changements caractérisant la composition de la végétation et les gradients environnementaux connexes relativement à sept bassins à boue du refuge d’oiseaux de l’île Kendall, dans le delta du Mackenzie. Trois décennies après la perturbation, la couverture végétale des bassins à boue était ...